COVID-19: Vicarious traumatisation and resilience in Mental Health Psychology Practitioners - Agata Wezyk; Ala Yankouskaya; Amanda Comoretto; Annita Ventouris; Constantina Panourgia; Zoe Taylor (University of West London, 2020)
Almost no nation has been spared as the novel coronavirus (COVID-19) has swept around the world. As the pandemic has upended much of society, frontline health care workers have shouldered much of the burden. Among other professionals, Mental Health Psychology Practitioners contribute significantly to fighting off the negative psychological effects of COVID-19, including distress, anxiety, and depression - provided they themselves can demonstrate resilience.